Correlation of Platelet-Derived Growth Factor-BB Levels as a Biomarker of Liver Fibrosis with the Degree of Fibrosis Based on Fibroscan in Chronic Hepatitis B Patients - Lumban Tobing, Richard Togi; Suyata; Mgs. Irsan Saleh (HM Publisher, 2024)
Background: Liver fibrosis is scar tissue that forms due to excessive accumulation of ECM proteins due to chronic liver injury, mediated by cytokines involving complex cellular interactions, such as platelet-derived growth factor-BB (PDGF-BB). In Indonesia, no research has been conducted to determine the correlation between PDGF-BB levels and the degree of liver fibrosis based on fibroscan. The aim of this study is to assess the correlation between PGDF-BB levels and the degree of liver fibrosis based on fibroscan in chronic hepatitis B. Methods: A cross-sectional study was conducted on the chronic hepatitis B population at the internal medicine clinic of Dr. Mohammad Hoesin General Hospital Palembang from January to Agustus 2023. The assessment uses fibroscan to determine the degree of liver fibrosis, measured in kilopascals (kPa). PDGF-BB levels measured by ELISA. Results: From 40 subjects, the majority of chronic hepatitis B patients were women (57,5%). The lowest PDGF-BB level was found in chronic hepatitis B patients with fibroscan F0, and the highest PDGF-BB level in fibroscan F4. Fibroscan results are directly proportional to PDGF-BB level. Conclusion: PDGF-BB has a strong positive correlation with the degree of fibroscan in chronic hepatitis B patients in Dr. Mohammad Hoesin General Hospital. The higher the range of PDGF-BB levels, the higher the degree of fibroscan in chronic hepatitis B patients.